2021
DOI: 10.3390/biomedicines9091245
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells and Cancer Stem Cells: The Jekyll and Hyde Scenario and Their Implications in Stem Cell Therapy

Abstract: “Jekyll and Hyde” refers to persons with an unpredictably dual personality, who are battling between good and evil within themselves In this regard, even cells consist of good and evil counterparts. Normal stem cells (NSCs) and cancer stem cells (CSCs) are two types of cells that share some similar characteristics but have distinct functions that play a major role in physiological and pathophysiological development. In reality, NSCs such as the adult and embryonic stem cells, are the good cells and the ultimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 125 publications
0
13
0
Order By: Relevance
“…Many studies have shown that in some forms of cancer, there are cells with specific stem-like properties called cancer stem cells (CSCs) [ 155 ]. CSCs are considered the “initiating” cells of the tumor and the main reasons behind tumor heterogeneity, resistance to therapy and recurrence [ 156 , 157 ].…”
Section: Parthenolide Selectivity In Tumor Cells and Targeting Cancer...mentioning
confidence: 99%
“…Many studies have shown that in some forms of cancer, there are cells with specific stem-like properties called cancer stem cells (CSCs) [ 155 ]. CSCs are considered the “initiating” cells of the tumor and the main reasons behind tumor heterogeneity, resistance to therapy and recurrence [ 156 , 157 ].…”
Section: Parthenolide Selectivity In Tumor Cells and Targeting Cancer...mentioning
confidence: 99%
“…However, CSCs can replicate and differentiate in an uncontrolled manner into populations of molecularly and phenotypically altered progenitor cells that may have limitless proliferative and survival potential with more plasticity than progeny of NSCs ( 13 ). Additionally, CSCs and NSCs possess high telomerase activity that prolongs their life span, express similar surface receptors and can stimulate angiogenesis ( 28 ).…”
Section: Cancer Stem Cells (Cscs)mentioning
confidence: 99%
“…NSCs develop through organogenesis to form internal organs, while CSCs have tumorigenic properties and form tumour tissues. Moreover, NSCs have normal karyotyping, whereas CSCs have abnormal karyotyping with genetic alterations ( 28 ). Characteristics of CSCs are summarised in Fig.…”
Section: Cancer Stem Cells (Cscs)mentioning
confidence: 99%
See 2 more Smart Citations